"It Was Like I Had Found My Tribe": Influence of a Neuroscience Outreach Program on High Achievers. (February 2017) - Dowie, Megan J.; Barrow, Mark; Nicholson, Louise F. B.
Engaging young people with science is essential to ensuring a scientifically literate society. Furthermore, it is important to enable access to a variety of sciences during adolescence, when individuals are making decisions about their future educational and career paths. The Brain Bee Challenge (BBC) is a quiz-based international neuroscience outreach program for high school students. We wished to determine what influence exposure to the scientific research environment had on the highest achievers' later choices in education, their career expectations, and their perspectives toward science. Semistructured interviews were carried out with seven of the past winners of the New Zealand National BBC finals. Analysis involved thematic coding to investigate the impact of BBC involvement and potential longer term consequences. Second-order coding found critical themes identified by participants. These themes highlight the value of research institution–led outreach activities that extend high achievers beyond the school curriculum. In addition to subject-specific influences, there were multiple benefits acknowledged at a personal or individual level, including socialization and identity development, further demonstrating the importance of such engagement activities.